2011
DOI: 10.1016/j.surg.2011.05.012
|View full text |Cite
|
Sign up to set email alerts
|

A single-institution review of 157 patients presenting with benign and malignant tumors of the ampulla of Vater: Management and outcomes

Abstract: Introduction While benign ampullary tumors are removed endoscopically, due to their potential to progress to malignant disease, the favored treatment for adenocarcinoma is pancreaticoduodenectomy. We reviewed our institution’s experience in order to identify which patients were at highest risk of disease progression following surgical resection, as well as evaluate whether localized T1 tumors are best treated by pancreaticoduodenectomy. Methods We retrospectively reviewed 157 patients who presented with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 25 publications
4
19
1
3
Order By: Relevance
“…When the lesions are large, en bloc resection is more difficult, and a piecemeal approach must often be adopted. In our material, the chance of finding an undiagnosed adenocarcinoma increased as the size of the lesion increased, an observation also reported by Hornick et al [32]. We found that increasing size was also associated with increased expression of mutated KRAS and, therefore, might indicate greater neoplastic potential.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…When the lesions are large, en bloc resection is more difficult, and a piecemeal approach must often be adopted. In our material, the chance of finding an undiagnosed adenocarcinoma increased as the size of the lesion increased, an observation also reported by Hornick et al [32]. We found that increasing size was also associated with increased expression of mutated KRAS and, therefore, might indicate greater neoplastic potential.…”
Section: Discussionsupporting
confidence: 87%
“…We, together with several others [16,30,32,33], have observed that obstructive jaundice at the time of presentation is frequently associated with an underlying, undiagnosed malignancy and a poor prognosis. Therefore, when patients present with jaundice, all efforts should be made to optimize preinterventional staging before decisions are made about definite treatment.…”
Section: Discussionmentioning
confidence: 71%
“…Die Autoren der Studie schlugen daher vor, dass Adenome >1,5 cm einer chirurgischen Therapie zugeführt werden sollten. Dieses Vorgehen konnte von einer weiteren Studie von Hornick et al [75] unterstützt werden.…”
Section: Indikationen Zur Endoskopischen Papillektomieunclassified
“…15,23–51 Among these, lymph node (LN) status has been identified as an important predictor of survival in multiple studies. 15,26–43 In those studies that found no association between LN involvement and prognosis, 25 the negative result is likely attributable to the variable definition of ampullary cancer.…”
mentioning
confidence: 99%